Antimicrobial photodynamic therapy in the treatment of aggressive periodontitis: a systematic review and meta-analysis. Issue 1 (January 2016) - Souza, Emmanuel; Medeiros, Ana; Gurgel, Bruno; Sarmento, Carlos
Abstract The aim of this systematic review was to investigate whether the use of antimicrobial photodynamic therapy (aPDT) as an adjuvant to scaling and root planning (SRP) yields better results than SRP alone or associated with systemic antibiotics in the treatment of aggressive periodontitis (AgP). A meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statements and Cochrane Collaboration recommendations. The search for relevant studies (earliest record to January 2015) was carried out in seven databases, followed by a manual search. Methodological quality assessment of the studies selected was based on an analysis of the risk of bias. At each time point of follow-up, the existence of significant differences (p  < 0.05) in clinical attachment level (CAL) gain and probing depth (PD) reduction (primary outcomes) between groups was assessed with RevMan software 5.0. Heterogeneity between studies was assessed by the Higgin test (I 2 ). Four randomized controlled trials (RCTs) satisfied the eligibility criteria of this review. Only one study was found to have a low risk of bias. There were no significant differences in PD reduction (mean difference 0.33, 95 % confidence interval −0.32 to 0.98, p  = 0.32) and CAL gain (mean difference 0.20, 95 % confidence interval −0.41 to 0.81, p  = 0.53) between the test and control interventions. At present, therefore, when compared to SRP alone or associated with systemic antibiotics, the evidence suggests that the association of aPDT + SRP is of no additional benefit in the nonsurgical treatment of AgP.